Legal Protection for Electricity Business Operators in Electricity Management to Achieve Business Fairness in Indonesia - Baron Fernando Simarmata; Huala Adolf; Elisatris Gultom (International Journal Labs, 2026)
Private sector involvement in electricity management in Indonesia faces significant legal hurdles following Constitutional Court decisions limiting the private sector's role. This research analyzes three main issues: first, the regulation of legal protection for business actors in electricity management; second, the implementation of legal protection for electricity business actors to realize business fairness; and third, the conceptual framework for legal protection embodying fairness in electricity business. This research employed normative juridical methodology using a descriptive analytical approach. Primary and secondary legal materials were examined through systematic interpretation of legislation, particularly Law No. 30/2009 on Electricity, Constitutional Court Decision No. 111/PUU-XIII/2015, and related implementing regulations. Qualitative juridical argumentation was applied without quantitative measurements. Three main findings emerge. First, legal protection provisions for business actors in electricity management lack clear and decisive regulation, as evidenced by legislation failing to position private business actors as primary subjects in electricity management. Second, the implementation of legal protection for electricity business actors in realizing business fairness remains inadequately accommodated within the current legal framework, where PLN maintains dominance. Third, the conceptual framework for legal protection embodying business fairness can be achieved through public-private partnership (PPP) implementation, requiring synchronization and harmonization of electricity regulations to position electricity businesses involving private participation as integral rather than merely supportive domains. Strengthening legal protection through regulatory reform and PPP frameworks is essential for achieving business fairness while maintaining constitutional principles of state control.